Business, Open Innovation and Art - Song, Beibei; Formica, Piero; Springborg, Claus (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
After its predecessors turned humans and organizations into machines, the Fourth Industrial Revolution is turning machines into humans. As digital machines acquire more and more cognitive intelligence, the development of humans becomes ever more vital, for society and business alike. Time has come to recognize the value of art and humanities. As the world experiences massive turbulence and companies find their "whitewater" environment increasingly complex to navigate, the 20th-Century mantras of efficiency, the bottom-line and shareholder value no longer suffice as proper guidance. New futures call for anticipatory creativity. Channeling inventiveness, aesthetics and a sense of meaning, art can be a powerful tool to catalyze innovation and transformation, helping companies (re)discover their compass, create new rafts to conquer the rapids, and find "blue ocean" market spaces in new world realities. Authored by multidisciplinary contributors brought together by editors BeiBei Song and Piero Formica, "Business, Open Innovation and Art" reflects a New Renaissance movement to revive humanness in the age of AI and harmony between man and nature. The research, case studies and experiments demonstrate a rich, multidimensional relationship between art and business, be it artistic strategies and processes, artful leadership, or art thinking for radical innovation. In this crucial phase of history, this book serves to advance the fundamental role of art and humanities, together with science and economics, for sustainable human enterprise.